2005
DOI: 10.1093/sleep/28.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Cyclic Alternating Pattern in Normal Preschool-Aged Children

Abstract: The analysis of CAP in preschool-aged children is characterized by an increase of CAP rate during slow-wave sleep and a high percentage of A1 phases and A2 phases. However, the lower percentage of A1 paralleled by an increase of A2 could represent a signal of higher sleep instability in this age group as compared with prepubertal school-aged children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 0 publications
0
16
1
4
Order By: Relevance
“…Moreover, another difference between our study and that of Miano et al. (2007) regards the children’s age, which we have kept within a narrow range in consideration of the age‐dependency of CAP parameters (Bruni et al. , 2002, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, another difference between our study and that of Miano et al. (2007) regards the children’s age, which we have kept within a narrow range in consideration of the age‐dependency of CAP parameters (Bruni et al. , 2002, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Sleep microstructure. CAP was scored according to the currently accepted criteria (Bruni et al, 2002(Bruni et al, , 2005Terzano et al, 2001), as shown in Table 1.…”
Section: Analysis Of Polysomnographic Recordingsmentioning
confidence: 99%
“…Rhythmic masticatory muscle activity (RMMA), physiologically characterizing SB, was found to be correlated with arousal activities [i.e., micro‐arousals and cyclic alternating pattern (CAP)] during sleep in children (Herrera et al , ) and in adults (Kato et al , ). Electroencephalographic (EEG) arousal does not change much with age in children (Scholle et al , ) while CAP phase A2 and A3, more related to RMMA, significantly decreased from preschoolers to school children (Bruni et al , , ; Terzano et al , ). This suggests that arousal fluctuation in children in relation to development can be a physiological factor underlying curvilinear changes of SB prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Parrino et al (2011) propose that specific configurations of this pattern could represent a marker of sleep instability. For instance, the prevalence in pre-school children (Bruni et al, 2005) and elderly subjects (Parrino et al, 1998) of desynchronized CAP phases (A2 subtype) over synchronized patterns (A1 subtype) would suggest a greater sleep instability in these age groups. Interestingly, A1 pattern displayed a significant increase in a post-training night, compared to baseline (Ferri et al, 2008), as well as a positive correlation with morning retest performance (Ferri et al, 2008; Aricò et al, 2010).…”
Section: Introductionmentioning
confidence: 99%